Executive Function Mediates the Relations between Parental Behaviors and Children's Early Academic Ability - Devine, Rory T.; Bignardi, Giacomo; Hughes, Claire (Frontiers in Psychology, 2016)
The past decade has witnessed a growth of interest in parental influences on individual differences in children’s executive function (EF) on the one hand and in the academic consequences of variation in children’s EF on the other hand. The primary aim of this longitudinal study was to examine whether children’s EF mediated the relation between three distinct aspects of parental behavior (i.e., parental scaffolding, negative parent-child interactions and the provision of informal learning opportunities) and children’s academic ability (as measured by standard tests of literacy and numeracy skills). Data were collected from 117 parent-child dyads (60 boys) at two time points approximately 1 year apart (M Age at Time 1 = 3.94 years, SD = 0.53; M Age at Time 2 = 5.11 years, SD = 0.54). At both time points children completed a battery of tasks designed to measure general cognitive ability (e.g., non-verbal reasoning) and EF (e.g., inhibition, cognitive flexibility, working memory). Our models revealed that children’s EF (but not general cognitive ability) mediated the relations between parental scaffolding and negative parent-child interactions and children’s early academic ability. In contrast, parental provision of opportunities for learning in the home environment was directly related to children’s academic abilities. These results suggest that parental scaffolding and negative parent-child interactions influence children’s academic ability by shaping children’s emerging EF.